2016
DOI: 10.1097/rlu.0000000000001152
|View full text |Cite
|
Sign up to set email alerts
|

Glioma Recurrence Versus Radiation Necrosis

Abstract: Our findings suggest that FET uptake with Cho/Cr ratio and normalized rCBVmean could be most useful to distinguish primary glioma recurrence from radiation necrosis. Hybrid simultaneous multiparametric F-FET PET/MRI might play a significant role in the evaluation of patients with suspected glioma recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Cho/Cr ratio accuracy was 97%, and combined 18 F-FET TBRmean, rCBV and Cho/Cr ratio produced the maximum area under the curve (AUC) (Jena et al, 2016). In more recent study by Hojjati et al (2018) to differentiate GBM recurrent from post-radiation necrosis, they found that combining the data from FDG-PET/MRI with the perfusion MRI resulted in an area under the curve of 1.0, indicating highest sensitivity and specificity (Hojjati et al, 2018).…”
Section: Prognosismentioning
confidence: 99%
“…Cho/Cr ratio accuracy was 97%, and combined 18 F-FET TBRmean, rCBV and Cho/Cr ratio produced the maximum area under the curve (AUC) (Jena et al, 2016). In more recent study by Hojjati et al (2018) to differentiate GBM recurrent from post-radiation necrosis, they found that combining the data from FDG-PET/MRI with the perfusion MRI resulted in an area under the curve of 1.0, indicating highest sensitivity and specificity (Hojjati et al, 2018).…”
Section: Prognosismentioning
confidence: 99%
“…For the differentiation of treatment-related changes from tumor relapse, amino acid PET also provides valuable diagnostic information. Using [ 18 F]FET or [ 18 F]FDOPA, especially the differentiation of radiation injury from tumor relapse in glioma patients, as well as in patients with brain metastases, can be obtained with a relatively high diagnostic accuracy between 80-90% ( Figure 2) [11,26,[67][68][69][70][71][72][73][74][75][76][77][78][79][80]. Importantly, in glioma patients, parameters derived from dynamic [ 18 F]FET PET acquisition may further increase the diagnostic accuracy [67,[74][75][76]78].…”
Section: Value Of Amino Acid Pet Tracers For Brain Tumor Patientsmentioning
confidence: 99%
“…However, TBRmax (or TBRmean) with Cho/Cr ratio yielded the highest accuracy, approaching up to 97%. Their findings suggested that FET uptake with Cho/Cr ratio and normalized rCBVmean could be most useful in distinguishing primary glioma recurrence from radiation necrosis [39].…”
Section: Brain Tumoursmentioning
confidence: 99%
“…The potential role of hybrid gadolinium (Gd)-enhanced FET-PET/MR in distinguishing brain tumour recurrence Ciarmiello et al from radiation necrosis was investigated by Jena et al [39]. They analysed twenty-six patients with single or multiple contrast-enhancing brain lesions on MR after surgery and radiation therapy.…”
Section: Brain Tumoursmentioning
confidence: 99%